Why Are the Wealthiest So Wealthy? A Longitudinal Empirical Investigation - Serdar Ozkan; Joachim Hubmer; Sergio Salgado; Elin Halvorsen (Center for Economic Studies and ifo Institute (CESifo), 2023)
We use Norwegian administrative panel data on wealth and income between 1993 and 2015 to study lifecycle wealth dynamics, focusing on the wealthiest households. On average, the wealthiest start their lives substantially richer than other households in the same cohort, own mostly private equity, earn higher returns, derive most of their income from dividends and capital gains, and save at higher rates. At age 50, the excess wealth of the top 0.1% group relative to mid-wealth households is accounted for in about equal terms by higher saving rates (34%), higher initial wealth (32%), and higher returns (27%), while higher labor income (5%) and inheritances (1%) account for the small residual. There is significant heterogeneity among the wealthiest: one-fourth of them–which we dub the "New Money"–start with negative wealth but experience rapid wealth growth early in life. Relative to the quartile of top owners that already started their life rich–the "Old Money"–the New Money are characterized by even higher saving rates and returns and also by higher labor income. Their excess wealth is mainly explained by higher saving rates (46%), higher returns (34%), and higher labor income (16%).
Keywords: D14; D15; E21; 330; wealth inequality; lifecycle wealth dynamics; rate of return heterogeneity; bequests; saving rate heterogeneity